Triathlete adapts to breathing restricted to the nasal passage without loss in VO2max or vVO2max - Hostetter, K.; McClaran, K. S. R.; Cox, D. G.; Dallam, G. M. (Journal of Sport and Human Performance, 2016)
This case study investigated the effect of restricting breathing to the nasopharynx versus the oropharynx on the ability to perform maximal and high level steady state running in a highly trained triathlete who previously adapted himself to nasal only breathing during exercise as a means of inhibiting exercise-induced bronchospasm (EIB). The subject was tested using a maximal graded treadmill protocol (GXT) to voluntary exhaustion followed 10 minutes later by a 6 minute steady state treadmill protocol (SS) at 85% of the previously achieved maximal velocity in both breathing conditions. Oxygen uptake was measured via indirect calorimetry and 1 second forced expiratory volumes (FEV1) were measured with spirometry. In the GXT trials the subject produced a time to exhaustion (TE) of 6:24, a maximal oxygen consumption (VO2max) of 3.92 L/min. and a velocity at VO2max (VVO2max) of 9.7 mph while breathing only through the nasopharynx (NB). While breathing only through the oropharynx (OB) he produced a TE of 6:15, a VO2max of 3.80 L/min. and a VVO2max of 9.7 mph.. During the 6 minute SS trials running at 8.0 mph, his mean oxygen consumption was 4.16 L/min. in NB and 3.99 L/min. in OB. The subject experienced a 17% reduction in FEV1 (Pre = 5.03 L/sec., Post = 4.17 L/sec.) following the OB GXT not seen following the NB GXT. This case study confirms the ability of a highly trained competitive triathlete to adapt to breathing restricted to the nasopharynx during running at both a maximal effort and a subsequent high level steady state effort without a loss in performance or peak aerobic capacity, as a means of inhibiting EIB.